Readiness, acceptance, and social presence in full online learning - Gaffar Hafiz Sagala; Ali Fikri Hasibuan; Tuti Sriwedari (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2022)
This study aimed to examine the effect of lecturer readiness in online learning on the acceptance of lecturers in online learning applications, and the effect of lecturer acceptance in online learning applications on the lecturer's perception of social presence. The subjects of this study were the lecturers at the Faculty of Economics, Universitas Negeri Medan which was taken by a total sampling technique. This study used a survey method with electronic questionnaires to collect data. Of the 113 lecturers, 81 responses were returned, and there were two incomplete questionnaires. This study had 79 responses that met the requirements of the analysis. The data were analyzed using Variance-based SEM. The results of the data analysis indicate that perceived usefulness is a critical variable in getting social presence in online learning. Meanwhile, the readiness of lecturers in online learning is an essential antecedent of the acceptance of the use of online learning applications